2011
DOI: 10.1177/0300985811414030
|View full text |Cite
|
Sign up to set email alerts
|

Intraepidermal Glandular Carcinoma of the Nipple (Mammary Paget-like Disease) in 2 Dogs

Abstract: Mammary Paget disease, characterized by diffuse infiltration of the nipple and areolar epidermis by carcinoma cells, develops in 1% to 3% of human mammary carcinomas. The purpose of this article is to present 2 cases of intraepidermal adenocarcinoma that resembled human mammary Paget disease, histologically and immunohistochemically, in dogs with underlying mammary carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The gross lesions had features that could be associated with Paget-like disease (ie, crusting and pigmentary changes) and scattered cells with clear cytoplasmic vacuoles ("signet ring" cells) can be a feature of Paget-like disease. 13 However, other features of Paget-like disease were not present in this study, including individual and small clusters of carcinoma cells in the epidermis of the teat 13 and underlying mammary carcinoma. 13 The presence of multiple teat lesions in some cases also helped to rule out Paget-like disease.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…The gross lesions had features that could be associated with Paget-like disease (ie, crusting and pigmentary changes) and scattered cells with clear cytoplasmic vacuoles ("signet ring" cells) can be a feature of Paget-like disease. 13 However, other features of Paget-like disease were not present in this study, including individual and small clusters of carcinoma cells in the epidermis of the teat 13 and underlying mammary carcinoma. 13 The presence of multiple teat lesions in some cases also helped to rule out Paget-like disease.…”
Section: Discussionmentioning
confidence: 52%
“…13 However, other features of Paget-like disease were not present in this study, including individual and small clusters of carcinoma cells in the epidermis of the teat 13 and underlying mammary carcinoma. 13 The presence of multiple teat lesions in some cases also helped to rule out Paget-like disease.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…It is interesting that among the described cases of male MGTs, 15 out of 74 (20.2%) were diagnosed in Crossbreeds (Arias et al 2015 ; Gopal et al 2022 ; Maiti et al 2014 ; Silva et al 2019 ) followed by Cocker Spaniels (18.9%) (Bearss et al 2012 ; Han et al 2016 ; Kwon et al 2017 ; Maiti et al 2014 ), German Shepherds (10.8%) (Machado et al 2020 ; Maiti et al 2014 ; Veena et al 2012 ), Labrador Retrievers (6.7%) (Bearss et al 2012 ; Lather et al 2017 ; Saba et al 2007 ) and Rottweilers (6.7%) (Machado et al 2020 ; Mamom et al 2012 ; Ramírez et al 2011 ; Saba et al 2007 ). Moreover, previous literature data indicated that Cocker Spaniels may be overrepresented among male dogs with MGTs (Bearss et al 2012 ).…”
Section: Mammary Gland Tumours In Male Dogsmentioning
confidence: 99%